COVID-19, the Global South and the Pandemic's Development Impact - McCann, Gerard; Mishra, Nita; Carmody, Pádraig (Bristol University Press, 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book examines the unique implications of the pandemic in the Global South. With international contributors from a variety of disciplines, it investigates the pandemic's effects on development, medicine, gender (in)equality and human rights among other issues. The book's assessment offers a discourse on the ways in which the impact of COVID-19 can be mitigated in some of the most challenging socio-economic contexts in the world.